PENINJAUAN FAKTOR-FAKTOR PENENTU RUMAH-TOKO DI SURABAYA DARI SUDUT PANDANG PENGEMBANG DAN PENGGUNA - Paulus Nugraha (Institute of Research and Community Outreach - Petra Christian University, 2000)
Before the Indonesian economic crisis at the end of 1997, shophouse was considered as the most attractive investment in Indonesian real estate. But the business abruptly came to a halt after the economic crisis, particularly after the news about riots and lootings in 1998. That is the reason of this research, which analyze factors which influence the shophouse characters, by accommodating the developers and the consumers' view. The developers' view was observed through the characteristics, while the consumers' view was observed through Kotler's